The economics of labor markets [7th ed.] - Kaufman, Bruce E.; Hotchkiss, Julie L. (Australia Thomson South-Western, 2006)
The best textbook for the in-depth study of labor market theories, THE ECONOMICS OF LABOR MARKETS helps you understand the background of the field as you explore its latest developments. Using built-in study aids and empirical research, the authors provide you an understandable introduction to labor economics. With sections on "In the News" and the most up-to-date data available, this version shows you how labor markets move the world. And after reading the industry-leading chapter reviews you'll be one step closer to success in the course.
Keywords: Labor economics; Economics